An insight into the environmental degradation caused by irregular occupations in green areas in the city of Manaus-AM (Research, Society and Development, 2021)
The urban structure of the capital of Amazonas changed with the urbanization process. As a result of this accelerated urbanization, Manaus, in the last three decades, has been facing a high number of irregular occupations, the so-called “invasions”. The problem becomes evident when we look at population demographic growth. This population growth was caused by the gigantic rural exodus and regional migrations, where huge populations were attracted mainly by the job opportunities in the Manaus Free Trade Zone. This paper considered what happened with two large irregular occupations in the city of Manaus in recent years, the occupation of the “City of Lights” and “Monte Horebe” and how the actions taken by the authorities impacted these irregular occupations. The impact of these irregular occupations, which flourish without any prior infrastructure and basic sanitation, has contributed to the degradation of important green areas for the city. The methodology used was the analysis of Google Earth Pro georeferencing data and data from the Annual Land Use and Coverage Mapping in Brazil. As a result, the repossession of Mount Horeb presented itself as a significant milestone in the repossession of irregular areas, as it was made possible through an agreement for the delivery of rental vouchers and the surveillance of the area, which was reoccupied for a purpose. social (in this case, a full-time school). It is already possible to see, even through satellite photos, that the degraded area is already recovering.